Epidemiological Analysis of Non-Communicable Diseases Post-Covid Era in Indonesia - Riski Dwi Prameswari; Natalia Christin Tiara Revita; Dwi Ayu Angraini; Islakhil Asfarina (GLOBAL HEALTH SCIENCE GROUP, 2025)
Non-communicable diseases (NCDs) are still a major health problem in the world and Indonesia. NCD prevention and control programs should be further improved to reduce NCD cases, especially in Indonesia. This study aims to analyze the risk factors for NCDs, prevention and control programs for NCDs in post-Covid Indonesia. Methods: This research is a mixed methods research (quantitative and qualitative) conducted in Surabaya, Sidoarjo and Gresik from July to September 2024. In quantitative research, the research sample was 400 people and analyzed using the Chi Square statistical test to see the risk factors for NCDs. In qualitative research, the research sample was 30 people from health workers, professional organizations and health offices in Surabaya, Sidoarjo and Gresik which were analyzed by content analysis. Data triangulation used in-depth interviews and Focus Group Discussion (FGD) methods. Results: The results showed that the factors associated with post-Covid NCD risk factors were knowledge level (p<0.05) and lifestyle factors (p<0.05). One factor that causes the promotion, prevention, and early detection of NCD programs to be less than optimal is the lack of public awareness of the importance of preventing NCDs. Conclusion: Suggestions for this study are to increase health promotion through information technology, increase the implementation of early detection of NCDs independently and control risk factors, especially at the level of knowledge and lifestyle of the post-Covid community.